Mortalidad Neonatal en el Hospital de Apoyo No. 3. Salud - Chepén - Mayo 1992 - Abril 1993 - Aguirre Romero, Enica Deneri (1994)
n order to determine the rate of neonatal mortality and Asociaci6n with maternal risk factors were studied 796 infants in the Hospital Support No 3 Health - Chepén, May 1992 - April 1993. The results were as follows: 1. The hospital Neonatal mortality rate was 11.3 per thousand live births. 2. The most important causes of neonatal death were: asphyxia, infection and congenital malformation, 3. The maternal risk factors associated with neonatal mortality was: RPM greater than 12 hours, placenta previa, polyhydramnios and prolonged expulsion. 4. The variables that contributed to the f1.1e neonatal mortality: Choking, prematurity and maternal disease.